MENITI JEJAK PENDUDUK ASLI TENGGARONG - Awang Muhammad Rifani (Prodi Administrasi Negara FISIPOL Universitas Kutai Kartanegara, 2012)
This Research tries to give explanation scientifically about the Source, History, Culture, Situation and Tenggarong’s native position in the past and contemporary which is almost could not understand and unrecognized by the most part of society.Thus, Tenggarong’s native people is kutai’s lampong society who has been living in Tepian Pandan for centuries, before the arriving king of kutai and new comer nowadays.It is proven by the history archive, site, artifact, language, and culture that have difference with most of kutai people.Key words: Tepian Pandan, Lampong, Kedang, Bengkuring, Bensamar.